2019
DOI: 10.1111/ijd.14575
|View full text |Cite
|
Sign up to set email alerts
|

Keloid patients have higher peripheral blood endothelial progenitor cell counts and CD34+ cells with normal vasculogenic and angiogenic function that overexpress vascular endothelial growth factor and interleukin‐8

Abstract: Background One suggested reason for aberrant wound healing in keloid scars is chronic inflammation of the dermis. We hypothesized that excessive blood vessel formation and high capillary density in keloid tissue is caused by dysfunction of endothelial progenitor cells. Methods We compared the number of circulating endothelial progenitor cells and vasculogenic and angiogenic capacity, as well as secretory function, of circulating CD34+ cells in keloid patients and healthy individuals. Results Compared to mononu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…A plethora of factors including IL-6, IL-8, IL-18, chemokine like factor-1 (CKLF-1), prostaglandin produced by cyclooxygenase (COX-1) that exhibit pro-inflammatory roles upon tissue damage have been found significantly elevated in keloid tissue (31,32). Even in the peripheral blood of keloid patients, IL-8 level was 7 fold higher than that of normal people (33). However, it is unclear that the rise of these soluble molecules is cause or consequence of keloid formation.…”
Section: Pro-inflammatory Effects and Scar Formationmentioning
confidence: 99%
“…A plethora of factors including IL-6, IL-8, IL-18, chemokine like factor-1 (CKLF-1), prostaglandin produced by cyclooxygenase (COX-1) that exhibit pro-inflammatory roles upon tissue damage have been found significantly elevated in keloid tissue (31,32). Even in the peripheral blood of keloid patients, IL-8 level was 7 fold higher than that of normal people (33). However, it is unclear that the rise of these soluble molecules is cause or consequence of keloid formation.…”
Section: Pro-inflammatory Effects and Scar Formationmentioning
confidence: 99%
“…These findings suggest that the high circulating EPC numbers in keloid patients may contribute to the immature nature of keloid capillaries. 16 Endostatin is the monomeric C-terminal proteolytic fragment of collagen XVIII. It is a very potent endogenous inhibitor of angiogenesis.…”
Section: Huang and Ogawamentioning
confidence: 99%
“…The treatment samples of our study revealed increased levels of growth factors such as FDF7, FGF10, TGF-beta, and VEGF. In particular, VEGF showed a profibrotic effect by multiple mechanisms (Tanaka et al, 2019 ). The use of talc enhanced the fibroproliferative pathway typical of hypertrophic scarring resulting in scars that directly activated inflammatory and fibrotic mediators fundamental to the human hypertrophic scarring process which is devoid of epidermal injury.…”
Section: Discussionmentioning
confidence: 99%